Impact of sleep‐disordered breathing on behavior and quality of life in children aged 2 to 7 years with non‐syndromic cleft lip and/or palate. Issue 10 (18th August 2021) - Moraleda‐Cibrián, Marta; Edwards, Sean P.; Kasten, Steven J.; Warschausky, Seth A.; Buchman, Steven R.; Monasterio‐Ponsa, Carme; O'Brien, Louise M.
Abstract: Introduction: Children with cleft are at high risk for sleep‐disordered breathing (SDB). However, little is known about the impact of SDB in this pediatric population. The aim of this study was to investigate whether SDB play a role in behavior and quality of life (QoL) in young children with cleft. Methods: Cross‐sectional study of 95 children aged 2.0–7.9 years with cleft palate. Parents completed a sleep (Pediatric Sleep questionnaire), a behavior (Conners' Early Childhood scale), and a generic health‐related QoL (KINDL questionnaire) assessment. Symptomatic children were referred for a polysomnography (PSG). Results: Overall, 14.7% of children (49.5% boys) screened positive for SDB and 27.4% had a PSG, which identified 84.6% with sleep apnea (apnea‐hypopnea index [AHI] ≥1) and 27.2% with AHI ≥5. Positive screening for SDB was associated with elevated T‐scores for anxiety and physical symptoms, significant differences in mean T‐scores for inattention/hyperactivity (64.2 ± 15.7 vs. 53.9 ± 11.4, p = .02), social functioning/atypical behaviour, social functioning (60.6 ± 11.7 vs. 51.9 ± 7.3, p = .004 and 59.5 ± 10.9 vs. 51.2 ± 8.0, p = .01) and mood (57.5 ± 8.2 vs. 50.7 ± 8.2, p = .03). Lower QoL scores for emotional and family well‐being were also reported in children with SDB (80.7 ± 13.4 vs. 90.0 ± 8.7, p = .01, 66.7 ± 15.8 vs. 76.9 ± 11.9, p = .04). Children with AHI ≥5 compared to those with AHI ≥1 and <5 showed significant differences in mean T‐score for aggressive behaviour (65.2 ± 12.1 vs. 52.3 ± 11.3, p = .04), defiant temper (62.8 ± 9.2 vs. 51.6 ± 10.2, p = .03) and lower family QoL scores (59.4 ± 15.2 vs. 77.1 ± 9.6, p = .006). Conclusions: In children with cleft palate the presence of SDB symptoms and moderate/severe sleep apnea was associated with behavioral (internalizing/externalizing) problems and lower family well‐being.